Large-Scale Seismic Vulnerability and Risk of Masonry Churches in Seismic-Prone Areas: Two Territorial Case Studies - Fabbrocino, Francesco; Vaiano, Generoso; Formisano, Antonio; D'Amato, Michele (Frontiers in Built Environment, 2019)
In this paper seismic vulnerability and risk of a sample of churches, located in Teramo and Ischia island (Naples gulf), both affected by the last Italian earthquakes, is presented. To this aim, it is applied a simplified assessment method particularly suitable for seismic evaluations at a territorial scale, providing a global score to be compared among the cases analysed. The data obtained allow us of plotting vulnerability maps and of providing a seismic risk index for all the considered churches. In addition, the calculated indexes permit a preliminary health state evaluation of the inspected churches, for ranking the priorities and planning additional in depth-evaluations.